Endoscopic transorbital approach to the cavernous sinus: Cadaveric anatomy study and clinical application (‡SevEN-009) - Jung, In-Ho; Yoo, Jihwan; Choi, Seonah; Lim, Seung Hoon; Ko, JaeSang; Roh, Tae Hoon; Hong, Je Beom; Kim, Eui Hyun (Frontiers in Oncology, 2022)
Objective: Cavernous sinus (CS) invasion is frequently encountered in the management of skull base tumors. Surgical treatment of tumors in the CS is technically demanding, and selection of an optimal surgical approach is critical for maximal tumor removal and patient safety. We aimed to evaluate the feasibility of an endoscopic transorbital approach (ETOA) to the CS based on a cadaveric study. Methods: Five cadaveric heads were used for dissection under the ETOA in the comparison with the endoscopic endonasal approach (EEA) and the microscopic transcranial approach (TCA). The CS was exposed, accessed, and explored, first using the ETOA, followed by the EEA and TCA. A dedicated endoscopic system aided by neuronavigation guidance was used for the procedures. During the ETOA, neurovascular structures inside the CS were approached through different surgical triangles. Results: After completing the ETOA with interdural dissection, the lateral wall of the CS was fully exposed. The lateral and posterior compartments of the CS, of which accessibility is greatly limited under the EEA, were effectively approached and explored under the ETOA. The anteromedial triangle was the largest window via which most of the lateral compartment was freely approached. The internal carotid artery and abducens nerve were also observed through the anteromedial triangle and just behind V1. During the ETOA, the approaching view through the supratrochlear and infratrochlear triangles was more directed towards the posterior compartment. After validation of the feasibility and safety based on the cadaveric study, ETOA was successfully performed in a patient with a pituitary adenoma with extensive CS invasion. Conclusions: Based on the cadaveric study, we demonstrated that the lateral CS wall was reliably accessed under the ETOA. The lateral and posterior compartments of the CS were effectively explored via surgical triangles under the ETOA. ETOA provides a unique and valuable surgical route to the CS with a promising synergy when used with EEA and TCA. Our experience with a clinical case convinces us of the efficacy of the ETOA during surgical management of skull base tumors with CS-invasion .